1998
DOI: 10.1038/381
|View full text |Cite|
|
Sign up to set email alerts
|

Cocaine self-administration in dopamine-transporter knockout mice

Abstract: The plasma membrane dopamine transporter (DAT) is responsible for clearing dopamine from the synapse. Cocaine blockade of DAT leads to increased extracellular dopamine, an effect widely considered to be the primary cause of the reinforcing and addictive properties of cocaine. In this study we tested whether these properties are limited to the dopaminergic system in mice lacking DAT. In the absence of DAT, these mice exhibit high levels of extracellular dopamine, but paradoxically still self-administer cocaine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
349
7
6

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 394 publications
(375 citation statements)
references
References 38 publications
13
349
7
6
Order By: Relevance
“…Moreover, they do not exhibit a general defect in learning. In a self-administration paradigm, where food is used as a reinforcer, DAT-KO mice are able to learn an operant behavior within the same training sessions as controls (Rocha et al, 1998). Similarly, KO mice are able to discriminate olfactory stimuli, and show no deficits in associative learning as tested in the place preference test (Sora et al, 1998;Rodriguiz et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they do not exhibit a general defect in learning. In a self-administration paradigm, where food is used as a reinforcer, DAT-KO mice are able to learn an operant behavior within the same training sessions as controls (Rocha et al, 1998). Similarly, KO mice are able to discriminate olfactory stimuli, and show no deficits in associative learning as tested in the place preference test (Sora et al, 1998;Rodriguiz et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, in interpreting the hyperdopaminergic state in DAT −/− mice one needs to consider potential compensatory responses in other neurotransmitter systems (i.e. NE or 5HT), which may have an impact on brain glucose metabolism (Rocha et al, 1998). Indeed, disulfiram, which is an inhibitor of the NE biosynthetic enzyme dopamine betahydroxylase, has demonstrated promising efficacy in the treatment of cocaine dependence in preliminary clinical trials (Weinshenker and Schroeder, 2007) and 5HT receptor-specific pharmacological compounds have been shown to reduce addictive properties of cocaine (Bubar and Cunningham, 2006).…”
Section: Cocaine Decreased Regional Bglum Differentially In Dat +/+ Amentioning
confidence: 99%
“…Microdialysis studies have reported significantly greater extracellular DA in DAT −/− mice than in DAT +/+ mice in the striatum and nucleus accumbens with estimates that the lifetime extracellular DA in DAT −/− mice is 300 times greater than in DAT +/+ littermates (Gainetdinov and Caron, 2003). Contrary to expected, while DAT −/− mice are resistant to cocaine's locomotor effects (Giros et al, 1996) they are sensitive to its rewarding effects (Rocha et al, 1998;Sora et al, 2001;Sora et al, 1998). Although these results led some to question the role of DAT in cocaine's reinforcing effects, the recent findings that cocaine's rewarding effects were abolished in transgenic mice with cocaine-insensitive DAT demonstrate the necessary role of DAT in cocaine's rewarding effects (Chen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This behavioral effect is produced primarily by inhibition of dopamine uptake, thereby increasing extracellular concentrations of released dopamine (Ritz et al 1987; for a review see Kuhar et al 1991;Spanagel and Weiss 1999). However, a recent study using mice lacking dopamine transporter proposed other mechanisms, such as increases in serotonin transmission, may mediate the reinforcing effects of cocaine (Rocha et al 1998).…”
Section: The Purpose Of This Study Was To Examine the Time Course Effmentioning
confidence: 99%
“…This behavioral effect is produced primarily by inhibition of dopamine uptake, thereby increasing extracellular concentrations of released dopamine (Ritz et al 1987; for a review see Kuhar et al 1991;Spanagel and Weiss 1999). However, a recent study using mice lacking dopamine transporter proposed other mechanisms, such as increases in serotonin transmission, may mediate the reinforcing effects of cocaine (Rocha et al 1998).Several studies have shown that cocaine also affects the expression of opioid peptides and opioid receptors. For example, chronic cocaine administration leads to increases in circulating ␀ -endorphin levels (Moldow and Fischman 1987), striatal preprodynorphin mRNA levels (Hurd et al 1992;Daunais et al 1993;Daunais and McGinty, 1995;Spangler et al 1993Spangler et al , 1996Spangler et al , 1997, and striatonigral dynorphin content (Sivam 1989;Smiley et al 1990) in rats and to decreases in preproenkephalin mRNA levels in rhesus monkeys (Daunais et al 1997) and humans (Hurd and Herkenham 1993).…”
mentioning
confidence: 99%